Increase Entrepreneurial Intentions: Proactive Personality, Entrepreneurship Education, and Academic Support as Predictors - Aryaningtyas, Aurilia Triani; Risyanti, Yustina Denik (Profesional Muda Cendekia Publishing, 2023)
This study conceptualizes entrepreneurship education and academic support as a moderator to understand the mechanism of the relationship between proactive personality and student entrepreneurial intentions. This study proposes a different proactive personality model as a variable influencing students' entrepreneurial intentions, with entrepreneurship education and academic support as a moderating variable. This influence model has never been studied, especially in Semarang. Some previous researchers tend to explore the influence of these factors separately. Observations from 192 students at ten universities in Semarang were used to test the hypothesized model. The study used a quota sampling technique and data collection was carried out by distributing questionnaires. The effect moderation model was tested using tiered regression analysis, with the Moderated Regression Analysis (MRA) interaction test. The results showed that the effect of proactive personality and entrepreneurial intentions of students was stronger when entrepreneurship education and academic support were included in the interaction. These findings are consistent with existing theory and studies. In addition, as a managerial implication, this study provides advice to tertiary institutions as educational institutions to consider proactive personality, entrepreneurship education, and academic support as necessary factors to encourage student interest in entrepreneurship. Entrepreneurship teaching methods should also be explored further.